ATC-NLSP: Prediction of the Classes of Anatomical Therapeutic Chemicals Using a Network-Based Label Space Partition Method - Wang, Xiangeng; Wang, Yanjing; Xu, Zhenyu; Xiong, Yi; Wei, Dong-Qing (Frontiers in Pharmacology, 2019)
Anatomical Therapeutic Chemical (ATC) classification system proposed by World Health Organization is a widely accepted drug classification scheme in both academic and industrial realm. It is a multi-labeling system which categorizes drugs into multiple classes according to their therapeutic, pharmacological and chemical attributes. In this study, we adopted a data-driven network-based label space partition (NLSP) method for prediction of ATC classes of a given compound within the multi-label learning framework. The proposed method ATC-NLSP is trained on the similarity-based features such as chemical-chemical interaction, structural and fingerprint similarities of a compound to other compounds belonging to the different ATC categories. The NLSP method trains predictors for each label cluster (possibly intersecting) detected by community detection algorithms and takes the ensemble labels for a compound as final prediction. Experimental evaluation based on the jackknife test on the benchmark dataset demonstrated that our method has boosted the absolute true rate, which is the most stringent evaluation metrics in this study, from 0.6330 to 0.7497, in comparison to the state-of-the-art approaches. Moreover, the community structures of the label relation graph were detected through the label propagation method. The advantage of multi-label learning over the single-label models was shown by label-wise analysis. Our study indicated that the proposed method ATC-NLSP, which adopts ideas from network research community and captures the correlation of labels in a data driven manner, is the top-performing model in the ATC prediction task. We believed that the power of NLSP remains to be unleashed for the multi-label learning tasks in drug discovery. The source codes are freely available at https://github.com/dqwei-lab/ATC.